Collaborative Governace in Post Earthquake Disaster Management on The Western Island of Java - Sri Wahananing Dyah; Eko Prasojo (JIAP (Jurnal Ilmu Administrasi Publik), 2020)
The geographical conditions of Indonesia which are on the Pacific Ring of Fire and are crossed by three world plates, the Eurasian plate, the Indo-Australian plate and the Pacific plate make Indonesia the most disaster-prone country, especially earthquakes. The large number of population in Indonesia contributes to the risk of life and social loss, physical loss, and economic loss. Based on this, the government seems to need more attention to disaster management efforts, which are multidimensional. On the other hand, disaster management in Indonesia have not yet become a national strategic issue and development goals so that resulting in disaster management in Indonesia are still not optimal due to the collaborative management processes that are not comprehensive and sustainable between the various levels of actors involved.The purpose of this study is to analyze collaborative governance in the prevention of earthquake reconstruction rehabilitation in the Western Island of Java. This study uses a post positivism approach with qualitative research methods through in-depth interviews and documentation studies.The results of this study indicate that it is needed: the objectives in post earthquake disaste management must consider providing solutions that can reach ordinary people, community independence and participation, human resources, technology, finance and legal as well as derivative rules, leader support, and collaboration between governments, non-governmental institutions, private sector, donor agencies, international agencies, universities and the community